Analisa Citra Merek, Kualitas Produk, Perluasan Merek Terhadap Kepuasan dan Loyalitas Pelanggan - Reni Fitria Nugraheni; Sampurno; Iha Haryani Hatta (JRB-Jurnal Riset Bisnis, 2020)
PT Kimia Farma Tbk, as one of the pioneers of the Indonesian pharmaceutical industry, is currently participating in the development of cosmetic products under the Marcks brand. Marcks' products are known to the public as powder, and always ranks third in the Top Brand title. The success of Marcks 'powder in dominating Top Brand has not been followed by other Marcks' products such as compact face powder, moisturizers and facial cleansers. This study aims to determine the effect of brand image, product quality, and brand extension on customer satisfaction and its impact on customer loyalty. This research is an explanatory research with a quantitative approach using a questionnaire as a research instrument. The population in this study were all Marcks product users who live in Jakarta. The sampling method is purposive sampling with a sample of 174 respondents. Data analysis uses the Structural Equation Modeling (SEM) LISREL 8.70 program. The results of the study explained that there is an influence between variable brand image, product quality and brand extension partially on customer satisfaction. However, brand image, product quality and brand extension have no effect on customer satisfaction. Customer satisfaction affects customer loyalty.